A comparative study of fuzzy logic-based models for groundwater quality evaluation based on irrigation indices - Vadiati, Meysam; Nalley, Deasy; Adamowski, Jan; Nakhaei, Mohammad; Asghari-Moghaddam, Asghar (Journal of Water and Land Development, 2019)
Abstract Groundwater quality modelling plays an important role in water resources management decision making processes. Accordingly, models must be developed to account for the uncertainty inherent in the modelling process, from the sample measurement stage through to the data interpretation stages. Artificial intelligence models, particularly fuzzy inference systems (FIS), have been shown to be effective in groundwater quality evaluation for complex aquifers. In the current study, fuzzy set theory is applied to groundwater-quality related decision-making in an agricultural production context; the Mamdani, Sugeno, and Larsen fuzzy logic-based models (MFL, SFL, and LFL, respectively) are used to develop a series of new, generalized, rule-based fuzzy models for water quality evaluation using widely accepted irrigation indices and hydrological data from the Sarab Plain, Iran. Rather than drawing upon physiochemical groundwater quality parameters, the present research employs widely accepted agricultural indices (e.g., irrigation criteria) when developing the MFL, SFL and LFL groundwater quality models. These newly-developed models, generated significantly more consistent results than the United States Soil Laboratory (USSL) diagram, addressed the inherent uncertainty in threshold data, and were effective in assessing groundwater quality for agricultural uses. The SFL model is recommended as it outperforms both MFL and LFL in terms of accuracy when assessing groundwater quality using irrigation indices.

Flood Risk Management: Exploring the Impacts of the Community Rating System Program on Poverty and Income Inequality - Noonan, Douglas S.; Sadiq, Abdul‐Akeem A. (Risk Analysis, 2018)
Abstract Flooding remains a major problem for the United States, causing numerous deaths and damaging countless properties. To reduce the impact of flooding on communities, the U.S. government established the Community Rating System (CRS) in 1990 to reduce flood damages by incentivizing communities to engage in flood risk management initiatives that surpass those required by the National Flood Insurance Program. In return, communities enjoy discounted flood insurance premiums. Despite the fact that the CRS raises concerns about the potential for unevenly distributed impacts across different income groups, no study has examined the equity implications of the CRS. This study thus investigates the possibility of unintended consequences of the CRS by answering the question: What is the effect of the CRS on poverty and income inequality? Understanding the impacts of the CRS on poverty and income inequality is useful in fully assessing the unintended consequences of the CRS. The study estimates four fixed‐effects regression models using a panel data set of neighborhood‐level observations from 1970 to 2010. The results indicate that median incomes are lower in CRS communities, but rise in floodplains. Also, the CRS attracts poor residents, but relocates them away from floodplains. Additionally, the CRS attracts top earners, including in floodplains. Finally, the CRS encourages income inequality, but discourages income inequality in floodplains. A better understanding of these unintended consequences of the CRS on poverty and income inequality can help to improve the design and performance of the CRS and, ultimately, increase community resilience to flood disasters.

Changes in cold region flood regimes inferred from long-record reference gauging stations - Burn, Donald H.; Whitfield, Paul H. (Water Resources Research, 2017)
Variability and nonstationarity in flood regimes of cold regions are examined using data from hydrometric reference streamflow gauging stations from 27 natural watersheds in Canada and adjacent areas of the United States. Choosing stations from reference networks with nearly 100 years of data allows for the investigation of changes that span several phases of some of the atmospheric drivers that may influence flood behavior. The reference hydrologic networks include only stations considered to have good quality data and were screened to avoid the influences of regulation, diversions, or land use change. Changes and variations in flood regimes are complex and require a multifaceted approach to properly characterize the types of changes that have occurred and are likely to occur in the future. Peaks over threshold (POT) data are extracted from daily flow data for each watershed, and changes to the magnitude, timing, frequency, volume, and duration of threshold exceedences are investigated. Seasonal statistics are used to explore changes in the nature of the flood regime based on changes in the timing of flood threshold exceedences. A variety of measures are developed to infer flood regime shifts including from a nival regime to a mixed regime and a mixed regime to a more pluvial-dominated regime. The flood regime at many of the watersheds demonstrates increased prominence of rainfall floods and decreased prevalence of snowmelt contributions to flood responses. While some individual stations show a relationship between flood variables and climate indices, these relationships are generally weak.

Le citoyen au coeur de la résilience dans l’agglomération de Montréal : lorsque l’adaptation au risque devient la préoccupation de chacun - Francès, Nathalie (2019)
La résilience, cette capacité d’une ville ou d’un environnement à maintenir sa structure, à s’organiser, apprendre et s’adapter aux chocs et stress, participe au mouvement de responsabilisation accrue du citoyen dans la protection contre les risques naturels. Si les inondations sont un phénomène récurrent à Montréal depuis la création même de la ville, les citoyens n’y sont encore que peu préparés comme le démontre l’ampleur des dommages causés par les inondations du printemps de 2017. Depuis le début du 21e siècle, les agences internationales et les États cherchent à sensibiliser le citoyen afin de susciter une action de sa part. On suppose alors que le citoyen informé aura ainsi une perception accrue des risques, conduisant au comportement de protection. Ce lien entre information, perception et comportement n’est pourtant pas évident. En réalité, la littérature montre que le comportement dépend d’une multiplicité de facteurs tels que l’expérience, la fréquence du risque ainsi qu’une évaluation par la personne de l’efficacité des mesures de protection, de leur coût face à une évaluation de la probabilité de la menace. Le mémoire vise à répondre à la question de recherche suivante : comment inciter les individus à adopter des mesures de protection contre les inondations à Montréal ? Une enquête auprès de 237 citoyens de quatre secteurs de l’agglomération touchés par les inondations printanières de 2017 met en lumière un ensemble d’obstacles à l’adoption des mesures de protection contre les inondations aujourd’hui analysés grâce au Protective Action Decision Model de Lindell et Perry (2012). Ainsi, dans le cas de Montréal, le manque d’action relève à la fois d’un manque d’information et de connaissances sur les origines du risque et les mesures de prévention, de la perception d’inefficacité des mesures comme la trousse 72 heures, d’une perception d’incapacité à mettre en place soi-même les mesures de prévention, et d’un coût important en ressources de ces dernières. Le dernier élément est l’incertitude de ce type de risque et l’incapacité à prévoir avec précision le prochain événement de crue, qui, combiné à un sentiment de responsabilité élevé des autorités à assurer la protection, implique un manque d’urgence à agir. Face à ces constats et après une étude du cas de la Nouvelle Orléans aux États-Unis, une réflexion est proposée sur les moyens à mettre en place pour inciter les citoyens à adopter ces mesures, comprenant sensibilisation mais aussi des moyens coercitifs et incitatifs.
Keywords: Site_internet_RIISQ

From Science to Policy and Practice: A Critical Assessment of Knowledge Management before, during, and after Environmental Public Health Disasters - Généreux, Mélissa; Lafontaine, Marc; Eykelbosh, Angela (International Journal of Environmental Research and Public Health, 2019)
Canada regularly faces environmental public health (EPH) disasters. Given the importance of evidence-based, risk-informed decision-making, we aimed to critically assess the integration of EPH expertise and research into each phase of disaster management. In-depth interviews were conducted with 23 leaders in disaster management from Canada, the United States, the United Kingdom, and Australia, and were complemented by other qualitative methods. Three topics were examined: governance, knowledge creation/translation, and related barriers/needs. Data were analyzed through a four-step content analysis. Six critical success factors emerged from the analysis: blending the best of traditional and modern approaches; fostering community engagement; cultivating relationships; investing in preparedness and recovery; putting knowledge into practice; and ensuring sufficient human and financial resources. Several promising knowledge-to-action strategies were also identified, including mentorship programs, communities of practice, advisory groups, systematized learning, and comprehensive repositories of tools and resources. There is no single roadmap to incorporate EPH expertise and research into disaster management. Our findings suggest that preparation for and management of EPH disaster risks requires effective long-term collaboration between science, policy, and EPH practitioners at all levels in order to facilitate coordinated and timely deployment of multi-sectoral/jurisdictional resources when and where they are most needed.
Keywords: Généreux_Mélissa

Mental health and retirement savings: Confounding issues with compounding interest - Bogan, Vicki L.; Fertig, Angela R. (Health Economics, 2018)
Summary The questionable ability of the U.S. pension system to provide for the growing elderly population combined with the rising number of people affected by depression and other mental health issues magnifies the need to understand how these household characteristics affect retirement. Mental health problems have a large and significant negative effect on retirement savings. Specifically, psychological distress is associated with decreasing the probability of holding retirement accounts by as much as 24 percentage points and decreasing retirement savings as a share of financial assets by as much as 67 percentage points. The magnitude of these effects underscores the importance of employer management policy and government regulation of these accounts to help ensure households have adequate retirement savings.
Keywords: Ouvrage_Collectif_Numéro1